Constraints that Hinder the Sustainability of Small Businesses in Durban, South Africa - Ayandibu, Ayansola Olatunji; Ngobese, Sindisiwe; Ganiyu, Idris Olayiwola; Kaseeeram, Irrshad (Journal of Reviews on Global Economics, 2019)
South Africa is viewed as one of the developing countries when compared to other African countries. However, the challenges that are experienced by the Small Business Enterprises (SMEs) continue to limit the economic growth of the country. Thus, these challenges are linked to the high rate of business failures. The main aim of the study is to evaluate constrains that hinder the sustainability of small businesses in Durban, South Africa. Employing the sociological entrepreneurship theory to understand the context of entrepreneurship and the challenges that pose a threat to the entrepreneurial activities, a qualitative approach was employed to achieve the objectives of study. A convenience sampling technique was employed to conduct in-depth interview among ten (10) entrepreneurs who participated in this study. NVivo 12 software was employed to analyse the data using a thematic and content analyses. The study findings revealed poor management, poor planning and lack of appropriate technology as some of the challenges confronting small businesses. Recommendations and conclusion are provided in this article.